Phytoremediation potential and copper uptake kinetics of Philippine bamboo species in copper contaminated substrate - Chua, Jennivee (Animo Repository, 2019)
The phytoremediation potential of three bamboo species, i.e. Bambusa merilliana, Bambusa blumeana, and Dendrocalamus asper, were evaluated for their total Cu uptake ability in hydroponics. Dendrocalamus asper proved to be the most efficient in terms of Cu phytoremediating potential with a constant positive uptake of 80 μM in a contaminated substrate and a bioconcentration factor of 50.57. Copper accumulation was found to concentrate the most in the roots compared to the amount translocated in the shoots. Analysis of the Cu uptake of D. asper roots at varying concentrations of Cu contamination (40, 80 and 120 μM) allowed for the fitting of the kinetics of Cu uptake and removal with existing kinetic models. The rate of copper removal per mass of plant was the best for the 0th order model in the 80 μM solution with an R2 of 0.954 and rate constant of 3.136 mg-kg−1d−1. The accumulation of Cu within the roots on day 7 (7d) followed the Michaelis–Menten model with an R2 of 0.970. The Michaelis–Menten constant (KM) was 4.87 mg/L and maximum accumulation velocity (Vmax) was 66.26 mg Cu-kg−1-day−1. Results suggest that D. asper is a potential hyperaccumulator plant that can be used in clean-up of domestic and industrial wastes present along river systems in the Philippines. © 2019 The Author(s)